ENGLISH AS А LINGUA FRANCA IN THE ERA OF GLOBALIZATION - О. В. Домніч (Записки з романо-германської філології, 2016)
The article investigates the English language, functioning as a lingua franca, in a modern multicultural and polyethnic universe in cross-cultural communication across the extrapolation of the secondary varieties of the given lingual system. The paper discusses history and meaning of the term “lingua franca”, characterizes its various definitions, describes the role, played by English, as an intermediary language in the distribution areas of the secondary varieties in contemporary community. The study also discusses functioning of lingua franca as a means of communication within multicultural ethnic communities. As a sociolinguistic term “lingua franca” does not have a unified definition and represents a variety of interpretations: “any language of wider interethnic communication”; certain types of “contact languages” used in interethnic communication; “verbal means of interethnic communication.” Having analyzed the problematics, we consider that in the era of globalization the English language has the status of macrointermediary language by virtue of the fact that it not only plays an intermediary role as in the context of certain nations, ethnic groups, but also covers the entire world community and is a global, world, polyethnic and multicultural one.